2017
DOI: 10.1007/s12551-017-0278-2
|View full text |Cite
|
Sign up to set email alerts
|

Alternative reagents to antibodies in imaging applications

Abstract: Antibodies have been indispensable tools in molecular biology, biochemistry and medical research. However, a number of issues surrounding validation, specificity and batch variation of commercially available antibodies have prompted research groups to develop novel non-antibody binding reagents. The ability to select highly specific monoclonal non-antibody binding proteins without the need for animals, the ease of production and the ability to site-directly label has enabled a wide variety of applications to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 106 publications
0
31
0
Order By: Relevance
“…While the implementation of fluorophores and fluorescent probes are an established method for visualization in vivo and in vitro, they face various limitations that can impact on the biological application studied or imaged, including interference with receptor signaling, cytotoxicity, and target specificity ( Table 2). Thus, the heavy reliance on these biochemical tools can create significant issues with imaging in vivo (187,188). Labelfree intravital imaging offers an exciting option to reduce this issue and will allow imaging of platelets and their structures in their physiological environment.…”
Section: Limitations Of Imaging In Living Organsmentioning
confidence: 99%
“…While the implementation of fluorophores and fluorescent probes are an established method for visualization in vivo and in vitro, they face various limitations that can impact on the biological application studied or imaged, including interference with receptor signaling, cytotoxicity, and target specificity ( Table 2). Thus, the heavy reliance on these biochemical tools can create significant issues with imaging in vivo (187,188). Labelfree intravital imaging offers an exciting option to reduce this issue and will allow imaging of platelets and their structures in their physiological environment.…”
Section: Limitations Of Imaging In Living Organsmentioning
confidence: 99%
“…To develop POLArIS, we sought a recombinant binder protein that has a helix available for tagging with GFP, as most of successful constrained tagging approaches used direct connection of the C-terminal α-helices of target molecules to the N-terminal 3 10 helix of GFP (Kampmann et al, 2011;Nakai et al, 2019;Mitchison, 2006, 2007). We found that Adhiron (the 20 nomenclature was later changed to "affimer" (Bedford et al, 2017)), a small protein (~12 kDa) with a consensus sequence of plant-derived phytocystatins (Tiede et al, 2014), has an α-helix at its N-terminus lying on top of four anti-parallel β sheets ( Figure 1A). Two variable peptide regions are inserted between anti-parallel β sheets ( Figure 1A) to create binding sites for an arbitrary molecule of interest, and phage-display screening is generally used for selecting Adhirons that specifically bind to target molecules (Hughes et al, 2017;Lopata et al, 2018).…”
Section: Gfpmentioning
confidence: 99%
“…We found that Adhiron (the 20 nomenclature was later changed to "affimer" (Bedford et al, 2017)), a small protein (~12 kDa) with a consensus sequence of plant-derived phytocystatins (Tiede et al, 2014), has an α-helix at its N-terminus lying on top of four anti-parallel β sheets ( Figure 1A). Two variable peptide regions are inserted between anti-parallel β sheets ( Figure 1A) to create binding sites for an arbitrary molecule of interest, and phage-display screening is generally used for selecting Adhirons that specifically bind to target molecules (Hughes et al, 2017;Lopata et al, 2018). We chose specific three Adhirons 14,and 24; for simplicity, we call them Ad-A, B, and C, respectively) that were reported to bind to F-actin in vitro (Lopata et al, 2016) as our initial 5 test case.…”
Section: Gfpmentioning
confidence: 99%
“…Unfortunately, such small probes exist only for a handful of targets 15 , while conventional 1.Abs are easily available for a large number of POIs. An alternative to the standard 2.Abs was recently developed: monovalent recombinant secondary nanobodies (2.Nbs) which were reported to reduce the linkage error observed in dSTORM 16 .…”
Section: Mainmentioning
confidence: 99%